ECONOMIC DEVELOPMENT PLANNING UNDER SCRUTINY: A TECHNICAL AND THEORETICAL DISCUSSION - Machado dos Santos, Adelcio; Antonio Córdova Ransolin, Marco; Tenconi, Daniel; Marton, Roberto; Sprandel da Silva, Solange (Revista Gênero e Interdisciplinaridade, 2026)
This article analyzes the planning of economic development, addressing its theoretical foundations, technical instruments, challenges, and limitations. Based on a review of classical and contemporary literature, the study discusses the conceptual fundamentals of development, the dimensions of planning, and the methodologies used to operationalize public policies and growth strategies. The relevance of macroeconomic models, projections, social accounting, geographic information systems, multiannual plans, and performance indicators as essential tools for guiding strategic decisions is highlighted. At the same time, limitations arising from institutional factors, economic uncertainties, environmental constraints, and social challenges are identified, emphasizing the need for integrated, flexible, and participatory approaches. The study underlines that economic planning cannot be reduced to technical procedures, as it must combine scientific rigor, institutional continuity, and sensitivity to distributive and sustainable dimensions. It concludes that, to be effective, planning must integrate quantitative and qualitative instruments, incorporate prospective scenarios, and include monitoring mechanisms, ensuring greater efficiency, equity, and sustainability. This work contributes to a critical understanding of planning as a strategic instrument for economic and social transformation, providing insights for researchers, public managers, and policymakers.